Prevalence of Hypertension, Overweight, and Obesity in Type 2 DM Patients Attending a Tertiary Health Care Facility in Enugu, Nigeria - Ijeoma Jacinta Nwagbara; Joel C Onyeanusi; Innocent SI Ogbu; Chikaodili Nwando Obi-Ezeani (Journal of Integrated Health Sciences)
Context: Diabetes mellitus (DM) is one of the noncommunicable diseases with an increased worldwide prevalence which differs from country to country. Hypertension and obesity may coexist in diabetes, thus enhancing complications and morbidities. Aim: The study determined the prevalence of hypertension, overweight, and obesity in type 2 DM patients attending a tertiary health care facility in Enugu, Nigeria. Setting and Design: A total of 296 type 2 DM patients attending the diabetes clinic at Enugu State University Teaching Hospital, Parklane, Enugu, were recruited for this study. Subjects and Methods: Blood pressure, weight, height, waist and hip circumferences were measured according to standard methods, waist to hip ratio and body mass index (BMI) were calculated. 3 ml of fasting blood sample was collected for blood glucose analysis. Statistical significance was considered at P < 0.05. Results: Of the 296 patients, 176 (59.5%) were female, whereas 120 (40.5%) were male. BMI was significantly higher in females when compared with the males (P = 0.002). The prevalence of hypertension was 36.8%, 35.2% in females and 39.2% in males. 26.7% were obese (30.1% females and 21.7% males) while 43.9% were overweight (42.6% females and 45.8% males). The prevalence rates of hypertension, overweight, and obesity were high in patients aged 56 years and above. Overweight and obese hypertensive patients had the prevalence rates of 45.9% and 40.4%, respectively. Conclusion: Hypertension and overweight or obesity persist in type 2 diabetic patients. The high prevalence of hypertensive overweight/obese diabetes patients calls for stringent measures through lifestyle modifications such as weight reduction, physical activity and dietary intake.